BUILDING MODERN JUSTICE BASED ON INFORMATION TECHNOLOGY (Study on Judicial Adaptation in the New Normal) - Andreas Eno Tirtakusuma; Astrid Prayogo Putri (Jurnal Hukum dan Bisnis (Selisik), 2021)
The COVID-19 pandemic has had an impact on the judiciary and the court system in Indonesia. The Covid-19 pandemic has accelerated the process of modernizing the existing judiciary by conducting online trials via video teleconference. Previously, with PERMA No. 3 of 2018 which was enhanced by PERMA No. 1 of 2019, the Supreme Court has implemented online trial services for civil cases. During the pandemic, online trials were also applied to the examination of criminal cases, which was carried out with PERMA No. 4 of 2020. In criminal cases, the implementation is limited only in certain circumstances and is carried out with the discretion of the judge/panel of judges who hears it. There are many benefits if an online trial is implemented at a time like this, to prevent the spread of the COVID-19 virus. However, there are still obstacles and there are rejections in its implementation, especially in online trials that are forced based on a judge's determination. The change in the trial system to an online method requires the role of law as a means to anticipate various things that have not yet happened (i.e. as social engineering) and law as a means to deal with changes that have occurred (i.e. as social control). One and another that aims to achieve legal expectations in providing certainty and justice